2004
DOI: 10.1016/j.pain.2004.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Amplitudes of laser evoked potential recorded from primary somatosensory, parasylvian and medial frontal cortex are graded with stimulus intensity

Abstract: Intensity encoding of painful stimuli in many brain regions has been suggested by imaging studies which cannot measure electrical activity of the brain directly. We have now examined the effect of laser stimulus intensity (three energy levels) on laser evoked potentials (LEPs) recorded directly from the human primary somatosensory (SI), parasylvian, and medial frontal cortical surfaces through subdural electrodes implanted for surgical treatment of medically intractable epilepsy. LEP N2* (early exogenous/stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
60
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 88 publications
13
60
1
Order By: Relevance
“…Other evidence is provided by the simultaneous pain-evoked activation of these areas which is consistently reported in neurophysiological recordings [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999]. The present study complements and extends these observations by showing directly the causal interactions, or better, the lack of causal interactions between these areas and thereby provides further confirmatory evidence for a parallel organization of S1 and S2 in human pain processing.…”
Section: Human Brain Mappingsupporting
confidence: 86%
See 1 more Smart Citation
“…Other evidence is provided by the simultaneous pain-evoked activation of these areas which is consistently reported in neurophysiological recordings [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999]. The present study complements and extends these observations by showing directly the causal interactions, or better, the lack of causal interactions between these areas and thereby provides further confirmatory evidence for a parallel organization of S1 and S2 in human pain processing.…”
Section: Human Brain Mappingsupporting
confidence: 86%
“…Traditional electrophysiological approaches inferred possible routes of information flow from the temporal order of activations. The results of these studies showed nearly simultaneous pain-evoked activations in S1, S2 and ACC [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999] which differ from more sequential activation patterns in other modalities and suggest a partly parallel organization of pain processing in the human brain. Other studies applied coherence analyses and showed pain-related changes in functional connectivity between brain areas related to pain [Llinas et al, 1999;Ohara et al, 2008;Ohara et al, 2006;Sarnthein and Jeanmonod, 2008].…”
Section: Introductionmentioning
confidence: 75%
“…Peripheral (Meyer et al, 2006) and spinal (Ferrington et al, 1987;Kakigi and Shibasaki, 1991) nociceptive afferents conduct at ϳ10 -20 m/s, whereas conduction velocities of tactile afferents amount to ϳ50 m/s (Vallbo et al, 1979). Consequently, in intracranial and extracranial recordings, earliest responses to selective nociceptive stimuli from the hand are typically recorded at ϳ120 ms (Ploner et al, 1999;Kanda et al, 2000;Ohara et al, 2004;Kakigi et al, 2005). Only recently, S1 responses to painful stimuli at latencies of ϳ90 ms have been reported (Inui et al, 2003), but even these latencies cannot explain our present observation of a 60 ms difference in central processing time between modalities.…”
Section: Discussionmentioning
confidence: 99%
“…These areas participate in different sensory, cognitive, and affective processes and, thus, differentially contribute to the experience of pain. Time courses of pain-evoked activations (Ploner et al, 1999;Kanda et al, 2000;Ohara et al, 2004) indicate that parts of this network are organized in parallel, which contrasts to the rather serial processing of other somatosensory information (Kaas, 2004). However, within this cortical network, processing times of behavioral responses to pain have remained essentially unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution is clearly responsible for the earliest identifiable peak in the obtained SEP waveforms (e.g., the N20 wave following stimulation of the median nerve) (Legatt and Kader 2000;Regan 1989). In contrast, although there is increasing evidence that S1 does contribute to nociceptive SEPs such as laser-evoked potentials (Schlereth et al 2003;Tarkka and Treede 1993;Valentini et al 2012), this contribution does not display the typical reversal of polarity over the central sulcus (Baumgartner et al 2011;Frot et al 2013;Kanda et al 2000;Ohara et al 2004a), suggesting that nociceptive and nonnociceptive somatosensory stimuli do not trigger responses within the same subregions of S1.…”
mentioning
confidence: 89%